5 - The Growth of Private Universities in Kenya: Implications for Gender Equity in Higher Education. - Onsongo, Jane (Journal of Higher Education in Africa, 2007)
The establishment of private universities in Kenya and Africa is relatively new. At independence (1960s) there were about seven universities on the continent. How- ever, by 2005 there were 85 private and 316 public universities in Africa (Kihara 2005). Kenya is leading in this expansion of private higher education in East Africa with 16 in 2006 compared to three in 1980. This article examines the implications of the growth of private universities on gender equity in higher edu- cation in Kenya. The article is based on two studies conducted in Kenya in 2002 and 2004 on the participation of women in university management. These two studies and a survey of literature on student enrolment in private and public uni- versities reveal that private universities are providing increased opportunities for women to access higher education both as students and staff. Increased opportuni- ties are provided through flexible admission and recruitment criteria, a conducive working environment and the appointment of more women into senior manage- ment positions.